IMPACT OF SKILLS DEVELOPMENT AND TRAINING ON JOB PERFORMANCE-A CASE STUDY IN THE INDUSTRY SECTOR IN IRAQ/BASRA - Abdulrazak Amer Adnan Alsadoon (Scholars Digest Publishing, 2024)
The present research examines the influence of skills development and training on job performance in the industrial sector, with a particular emphasis on the connections across skills and competencies, employee perception, actionable insights, and overall job performance. Using a statistical approach, we gathered information from three hundred staff members using organized questionnaires. We measured significant factors like stages of skills proficiency, employee happiness, the effectiveness of training received, and self-assessed job performance. The statistical analysis indicated that staff members typically had a good opinion of their skills and competences, via a notable number reflecting high levels of job performance. A regression analysis revealed that enhanced applied assistances and perspectives were significantly correlated with increased jobs satisfactions. The importance of individuals' viewpoints in the management of this connections have been underscored. The results suggest that individual training programmes are crucial for increasing employee engagements, fostering personal skill development, and ensuring subject matter mastery. The essay argues that companies should support their employees' professional development by providing them with opportunities for continuous learning, allocating technological resources for training, and fostering a healthy work environment. Businesses have a golden opportunity to increase employee productivity and reach their goals.
Keywords: Skills Development and Competencies, Employee Perception, Actionable Insight, Job Performance, Industrial Sector